1999
DOI: 10.1107/s0021889899011103
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties ofp+-type porous silicon layersversusthe substrate orientation: an X-ray diffraction comparative study

Abstract: The structural properties of (001)-and (111)-oriented p + -type porous silicon samples have been investigated using X-ray techniques. X-ray re¯ectivity applied to thin layers of both orientations allows the estimation of the layer thickness, the porosity and the interface roughness. High-resolution X-ray diffraction was used to obtain symmetrical and asymmetrical rocking curves, as well as maps of the reciprocal space. The lattice-mismatch parameter was measured and some indications about the pore shape, orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…1). XRSM of pSi prepared from the substrates HP-HT treated at 1230 K at 1 GPa indicated much enhanced isotropic diffuse scattering suggesting the presence of very small oxygen clusters [3] in pSi and of isotropic pores [5]. These results well correlate with the absorption measurements (a distinct absorp- tion line at %1230 cm ±1 was observed which is related to the presence of small plateletor spherical-like oxygen precipitates) [6].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…1). XRSM of pSi prepared from the substrates HP-HT treated at 1230 K at 1 GPa indicated much enhanced isotropic diffuse scattering suggesting the presence of very small oxygen clusters [3] in pSi and of isotropic pores [5]. These results well correlate with the absorption measurements (a distinct absorp- tion line at %1230 cm ±1 was observed which is related to the presence of small plateletor spherical-like oxygen precipitates) [6].…”
Section: Resultssupporting
confidence: 77%
“…XRSM proved considerable strain for the pSi/Si samples prepared from the A-type substrate annealed at 1620 K for 30 min at 10 5 Pa (relative change of lattice parameter Da/a % 10 ±4 , close to that reported in [5]), whereas almost no stress was detected for pSi/Si prepared from Cz-Si treated at 1620 K for 30 min at 1 GPa (Fig. 4).…”
Section: Resultsmentioning
confidence: 75%
“…The important methods of characterization of porous layers and epitaxial layers grown on porous layers are X-ray diffraction methods accompanied by scanning and the transmission electron microscopy as demonstrated in the previous studies. [14][15][16][17][18][19][20][21][22] The characteristic effect observed by means of X-ray diffraction is a significant increase of interplanar distances in the porous layer, as well as the small width of the diffraction maxima coming from the porous layer comparable with those of ideal crystals. [14][15][16][17] The formation of interference maxima connected with the porous layer had also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] The characteristic effect observed by means of X-ray diffraction is a significant increase of interplanar distances in the porous layer, as well as the small width of the diffraction maxima coming from the porous layer comparable with those of ideal crystals. [14][15][16][17] The formation of interference maxima connected with the porous layer had also been reported. [18] The influence of wetting of the porous layer changes of interplanar distances was reported in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in a porous material with a high degree of crystal lattice coherence one can use the intensity of X-ray diffraction to obtain information on the thickness, deformation and statistical Debye-Waller factor, and on the degree of porosity in the layers. For the parameters of the pores and for crystallites that are displaced from coherent positions, only the form and angular spread of the diffuse scattering has been analyzed so far (Faivre & Bellet, 1999). A quantitative analysis of pores, their geometrical form, fractality, ordering and space distribution was never implemented owing to the vast number of free parameters in the model.…”
Section: Introductionmentioning
confidence: 99%